The City from the Wire the Aerial Cable Transport for the Urban Mobility - Fistola, Romano (TeMA - Journal of Land Use, Mobility and Environment, 2026)
The urban transfer by using ropeways can produce impacts and externalities which, if well-managed, can trigger processes reliever, sustainable development and promoting tourism inside the city. The article starts from the consideration of urban transport by ropeways as a viable, effective alternative to the collective transfer among different areas of the city, particularly in those cities characterized by unique morphological or hydrographic territory which are fit for being overcome by mobility systems at high altitude. These features, in many international urban contexts, also contribute to enhance the amenity and the urban appeal. The paper intends to underline how the ropeways can become an efficient urban transport system between urban sites, often placed at different heights and for which there is a less accessibility by ground, and at the same time, a fascinating way of tourist mobility that allow people to observe the city from above (moving on it), in a sort of dynamic view. This interesting functional convergence has been often highlighted in the studies conducted on this mode of transportation, ,which in the past was considered one of the real possibilities for urban moving. Many cities are characterized by this type of mobility and within which existing systems of lifts, oblique connections between parts of the city are provided by urban systems, lifts, cable cars, escalators, moving walkways, etc.. A focus is also provided in relation to the ropeways, currently operating in many cities around the world, highlighting the effectiveness of mobility solutions at high altitude, although not necessarily intended for the slope, taken in metropolitan contexts outside of Europe since the Seventies. Furthermore a specific attention it is payed to the plants currently disused in Turin and in Naples with a special regard to the possible recovery prospects in a new urban mobility system. For the city of Naples it is presented also a new project for a rope way between the two famous museums: the Archeological Museum, which is located inside the inner city, and the Capodimonte one which is at top if the hill of Capodimonte inside the well known area of the royal palace. Finally some new projects are presented regarding the cities of Rome and Milan. For the two biggest Italian cities there are two ropeways designed that will, in the case of Milan, link urban areas along a path that includes interchanges and stations in major urban hubs, starting from the airport; in the case of Rome the “link” will cross the river Tevere in order to connect two large districts of the city: the EUR and Magliana, historically splitted by the barrier river".